Effect of Topical Erythropoietin (EPO) on palatal wound healing subsequent to Free Gingival Grafting (FGG) - Siamak YAGHOBEE; Nina ROUZMEH; Hoori ASLROOSTA; Sanaz MAHMOODI; Afshin KHORSAND; Mohamad Javad KHARRAZIFARD (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Free gingival grafting, the most predictable technique to increase the keratinized gingiva, leaves an open wound on the palate and the resulting discomfort during the healing phase is a significant concern. This study was intended to evaluate the effect of topical erythropoietin on healing of the donor site. Twelve patients lacking an attached gingiva at two sites in the mandible were included. In the test group, 1 mL of gel containing erythropoietin at a concentration of 4,000 IU mL-1 was applied to the donor site, whereas the control group was treated with 2 mL of the gel alone. On the second day after surgery, the same procedure was repeated. H2O2 was used to evaluate the amount of epithelialization. Clinical healing was compared using photographs and direct examination. The EPO group showed significantly better keratinization only on day 21. Comparison of clinical healing based on direct examination revealed significantly better healing in the test group on day 28. Furthermore, inflammation in the test group was lower than in the control group on the same day. Topical application of EPO improves palatal wound healing during the third and fourth weeks after free gingival graft procedures.